2006
DOI: 10.3310/hta10040
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness and cost-effectiveness of neuroimaging assessments used to visualise the seizure focus in people with refractory epilepsy being considered for surgery

Abstract: Non-UK purchasers will have to pay a small fee for post and packing. For European countries the cost is £2 per monograph and for the rest of the world £3 per monograph.You can order HTA monographs from our Despatch Agents:-fax (with credit card or official purchase order) -post (with credit card or official purchase order or cheque) -phone during office hours (credit card only).Additionally the HTA website allows you either to pay securely by credit card or to print out your order and then post or fax it. NHS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
65
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 33 publications
(141 reference statements)
1
65
0
Order By: Relevance
“…An association between hypoperfusion in the interictal SPECT and hyperperfusion in the ictal SPECT was the commonest finding during the PSAE 16 . however we found variations such as hyperperfusion in the interictal SPECT, even when no seizures were identified within the previous 24 hours or of Periodic Lateralized Epileptiform discharges (PLEd), which may be responsible for this change in the scintigraphic pattern as has been reported in publications in approximately 5% of interictal studies 14 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between hypoperfusion in the interictal SPECT and hyperperfusion in the ictal SPECT was the commonest finding during the PSAE 16 . however we found variations such as hyperperfusion in the interictal SPECT, even when no seizures were identified within the previous 24 hours or of Periodic Lateralized Epileptiform discharges (PLEd), which may be responsible for this change in the scintigraphic pattern as has been reported in publications in approximately 5% of interictal studies 14 .…”
Section: Methodsmentioning
confidence: 99%
“…Refractory epilepsy patients generally present with a scintigraphic pattern of cerebral hypoperfusion 11,12 , normal cerebral perfusion 13 or, infrequently, hyperperfusion 14 during the interictal period (outside of seizure) and cerebral hyperperfusion 11,[15][16][17] of the same area during the ictal period (during the seizures).…”
mentioning
confidence: 99%
“…Several reports in the past have indicated that PET is safe and may benefit a subset of patients undergoing surgery, [4][5][6] whereas another report concluded that there is a lack of evidence on the effectiveness and cost-effectiveness of imaging techniques (including PET) in the presurgical workup to inform clinical practice. 7 As a result, the purpose of the present study was to systematically review the literature to assess the diagnostic accuracy and clinical utility of PET in the presurgical evaluation of adult and pediatric patients with medically intractable epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…34 In the evaluation of diagnostic technologies used in the work-up for epilepsy surgery, the need for follow-up studies to quantify the effect of a diagnostic technology on patient outcome is particularly important because a reliable independent reference standard is not available. 36,37 The prior HTA report highlighted further serious limitations with the data from the diagnostic accuracy studies in imaging technologies used in the work-up for epilepsy surgery: ■ There is no established, reliable, reference standard test against which a new test can be compared.…”
Section: Prior Researchmentioning
confidence: 99%
“…In 2006, an HTA report 36 was published of a broad-ranging systematic review that evaluated neuroimaging technologies used to identify the seizure focus in patients with refractory epilepsy being considered for surgery. The prior HTA report highlighted a number of limitations of the evidence available at that time.…”
Section: Prior Researchmentioning
confidence: 99%